2011
DOI: 10.1007/s00424-011-1042-2
|View full text |Cite
|
Sign up to set email alerts
|

Sleep, vigilance, and thermosensitivity

Abstract: The regulation of sleep and wakefulness is well modeled with two underlying processes: a circadian and a homeostatic one. So far, the parameters and mechanisms of additional sleep-permissive and wake-promoting conditions have been largely overlooked. The present overview focuses on one of these conditions: the effect of skin temperature on the onset and maintenance of sleep, and alertness. Skin temperature is quite well suited to provide the brain with information on sleep-permissive and wake-promoting conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 84 publications
1
63
0
Order By: Relevance
“…S1) and we saw a similar pattern in the Tsimané. Therefore, we precisely measured ambient temperature at the sleeping sites along with finger temperature and abdominal temperature in our studies of the San[21]. Figs.…”
Section: Resultsmentioning
confidence: 99%
“…S1) and we saw a similar pattern in the Tsimané. Therefore, we precisely measured ambient temperature at the sleeping sites along with finger temperature and abdominal temperature in our studies of the San[21]. Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Diverse theories have been proposed to clarify the thermophysiological mechanism leading to sleep initiation. Over the past decades, the influence of altering core body temperature, body heat production and/or heat loss have been studied as potential processes involved in the circadian regulation of the sleep‐wake cycle . Currently, it is assumed that the redistribution of heat from proximal to peripheral sites, driven by vasodilation of distal skin regions, is a crucial step and it is closely linked to sleep onset latency .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown the relationship between indoor climate and the quality of sleep [27][28][29][30][31][32][33], stating that the optimal thermal conditions for a good night's sleep are different from ASHRAE 55 [27,28]. For example, research indicates that in the summer indoor temperatures during sleep could be higher than those prescribed by ASHRAE 55.…”
Section: Introductionmentioning
confidence: 92%
“…A c c e p t e d M a n u s c r i p t 33 Lee et al [347] studied the descriptors -warm‖ and -slightly hot‖, when translated from English to Korean and used in scales to assess the thermal comfort sensation. Results indicate that for Koreans, the term -warm‖ indicates thermal comfort, while -slightly hot‖ refers to some sort of discomfort [347].…”
Section: Thermal Comfort In Other Indoor Environmentsmentioning
confidence: 99%